2014
DOI: 10.1063/1.4870921
|View full text |Cite
|
Sign up to set email alerts
|

Thermal desorption mass spectrometer for mass metrology

Abstract: This article presents a device for the study of physisorbed elements on polished surfaces (diameter ⩽56 mm) of the kind used in mass metrology. The technique is based on mass spectrometry of molecules desorbed after heating under vacuum of the analyzed surface. We describe a first application of the device to study current and future mass standards in order to understand how their surface reactivity depends on storage conditions, cleaning processes, and polishing methods. Surface contamination analysis by ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…The current results lead to conclusions similar to those by Silvestri et al [102] in their TDS-GU study of iridium mass standards. They found that water constituted the major component of the spectra obtained after the samples were cleaned following the recommended procedure [103] and then exposed to the laboratory atmosphere.…”
Section: Accepted Manuscriptsupporting
confidence: 91%
“…The current results lead to conclusions similar to those by Silvestri et al [102] in their TDS-GU study of iridium mass standards. They found that water constituted the major component of the spectra obtained after the samples were cleaned following the recommended procedure [103] and then exposed to the laboratory atmosphere.…”
Section: Accepted Manuscriptsupporting
confidence: 91%
“…Silvestri et al [42] determined the water desorption activation energy E D for pure iridium after BIPM cleaning, exposure to air for 10 d and finally, thermal desorption under vacuum (heating ramp of 50 °C • min −1 from ambient temperature up to 600 °C). They found a value E D of 0.43 eV with a standard uncertainty of 0.02 eV.…”
Section: Study Of the New Materials: Iridium And Udimet 720mentioning
confidence: 99%
“…toluene, cyclohexane, and dichloromethane). TDS is a method used to observe how molecules and atoms bound to the surface of materials are released from the surface as the surface temperature increases, and is used to evaluate material design, surface contamination, and manufacturing processes [32][33][34].…”
Section: Introductionmentioning
confidence: 99%